2007
DOI: 10.1097/shk.0b013e31802b5d9f
|View full text |Cite
|
Sign up to set email alerts
|

MICE DEPLETED OF Αβ BUT NOT Γδ T CELLS ARE RESISTANT TO MORTALITY CAUSED BY CECAL LIGATION AND PUNCTURE

Abstract: The present study was undertaken to determine whether the mice depleted of alphabeta or gammadelta T cells show resistance to acute polymicrobial sepsis caused by cecal ligation and puncture (CLP). T-cell receptor beta knockout (betaTCRKO) and T-cell receptor delta knockout (deltaTCRKO) mice were used. An additional group of mice was treated with an antibody against the alphabeta T-cell receptor to induce alphabeta T-cell depletion; a subset of alphabeta T cell-deficient mice was also treated with anti-asialoG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
2
21
1
2
Order By: Relevance
“…It cannot be ruled out, however, that the antiinflammatory effects of rsCD6 on LPS-induced septic shock may also result from its inhibitory effects on different cell subsets involved in the outcome of sepsis such as CD8 T cells and natural killer cells (35). In fact, rsCD6 has been shown to inhibit human antigen-presenting cell-T cell interactions (17,36), and CD6 is known to be expressed on natural killer cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be ruled out, however, that the antiinflammatory effects of rsCD6 on LPS-induced septic shock may also result from its inhibitory effects on different cell subsets involved in the outcome of sepsis such as CD8 T cells and natural killer cells (35). In fact, rsCD6 has been shown to inhibit human antigen-presenting cell-T cell interactions (17,36), and CD6 is known to be expressed on natural killer cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Ratones defi cientes de células NK que cursan con un proceso de sepsis son más resistentes a la muerte inducida por este síndrome, lo cual fue asociado a la atenuación de la respuesta infl amatoria 38,39 . De hecho, la activación de las células NK induce la secreción de citoquinas como IFN- y FNT-, que contribuyen a la falla multisistémica y al cuadro clínico del shock séptico.…”
Section: Células Asesinas Naturales (Nk)unclassified
“…Ratones defi cientes de esta población celular son más susceptibles a desarrollar sepsis, lo que se ha asociado con una disminución plasmática de citocinas pro-infl amatorias como IFN- y FNT-, así como al establecimiento de un estado de imununosupresión que contribuye a la mortalidad de estos ratones 60,61 . En contraste, en otros estudios no se ha observado un efecto en la supervivencia o producción de citoquinas en ratones defi cientes de LTgd que cursan con un proceso de sepsis (LPC) 38 , mientras que en otros se sugiere que la defi ciencia de LTgd disminuye la morbilidad de ratones que cursan con infecciones bacterianas 62 . Adicionalmente, algunas alteraciones en la función y en el porcentaje de esta población celular se han observado en pacientes con shock séptico y trauma 63,64 .…”
Section: Linfocitos T Gamma/delta ()unclassified
“…Our group identified that Arid5a, which is a counteractive partner to Regnase-1, is a stabilizer in terms of binding to the 3'-UTR of IL-6 mRNA [5]. The expression of Arid5a is quickly induced in macrophages upon LPS stimulation ( Figure 1).…”
mentioning
confidence: 99%
“…However, exaggerative elevation of cytokine production might lead to the onset or development of acute inflammatory diseases. Sepsis is severe systemic inflammatory response upon infection, leading to excessive pro-inflammatory cytokine production such as IL-6, TNFα and IFNγ [4,5]. Upon infection, IL-6 and TNFα are highly expressed by innate immune cells including macrophages and dendritic cells, whereas IFNγ is produced by IL-12−derived T helper type 1 (Th1) cells.…”
mentioning
confidence: 99%